Implementation of Problem-Based Learning Model in Teaching Proclamation History to Grade XII-AKL Students - Hafiz Fajar Dwi Putra; Romadi (Journal of Practice Learning and Educational Development, 2026)
Problem-Based Learning (PBL) equips students to analyze primary and secondary historical sources, compare event versions, identify perspective differences, and build evidence-based historical arguments. This approach critical thinking, source evaluation, interpretation skill, and collaboration skills. PBL aligns perfectly with history curricula by integrating real-world contexts, diverse resources, and critical reasoning, making lessons meaningful and relevant to 21st-century competencies like collaboration, digital literacy, problem-solving, and reflective thinking. This study use a descriptive qualitative approach to deeply explore PBL implementation in teaching "Various Important Events Surrounding the Proclamation" to Grade XII-AKL students at SMK Dian Kartika Semarang. Qualitative methods capture social phenomena in natural situations, enabling comprehensive insights into learning processes and student responses. Findings reveal that educators at Dian Kartika Vocational School effectively implement PBL, despite minor discussion-phase challenges.